Organizational Culture and its Influences on Work Performance - Dr. R Rajendran, Sasidharan M (International Journal of Control and Automation, 2020)
This study aims to assess direct and indirect influences of organizational culture on work performance, as well as to evaluate the impact of each sub element of organizational culture on such performance. It is argued that work performance derives, on the one hand, from a long-term perspective related to changes that organizations manage and implement during their process of growth. The dimension of organizational culture can be given through organizational values, routines and distinctive aspects of culture that allow organizations to create competitive advantages. The quantitative research (survey) has been chosen in order to meet the purpose of the research and to test those relationships empirically; the data is collected from structured questionnaire. Sample size is 210 and also Descriptive research study is used as a research design and followed simple random sampling method. the sample was selected from various information technology companies being operative in Chennai. These findings indicate a positive relationship between organizational culture and work performance. Likewise, four organizational culture sub-elements, namely Managing Change, Achieving Goals, Coordinating Teamwork and Cultural Strength, were found affecting positively on work performance, but with varying and distinct intensity.